Pemodelan Genangan Banjir Sub DAS Bengkulu Hilir Provinsi Bengkulu Menggunakan Program Hec-Ras 5.0.7 Berbasis Ras Mapper dan Arc-Gis 10.8 - Gunawan, Gusta; peri, Bes; Misliniyati, Rena; Trie Saputra, Iqbal Kurnia; patrianusa, Iqbal; Aqilah, Hauranda (Department of Civil Engineering, Diponegoro University, 2023)
The Down Stream Air Bengkulu Watershed is part of the Air Bengkulu Watershed in Bengkulu Province. Flooding in this area frequently leads to major subdistrict, economy, and environmental impacts. The aim of the research is to develop a flood forecasting model that is capable of mapping potential flood areas in order to support flood control efforts. The method used is a hybrid model between a hydrological model, a hydraulics model and a Geographic Information System (GIS). The hydrological model is input to HEC-RAS software, It’s developed based on Snyder's Synthetic Unit Hydrograph (SUH). The hydraulics model was prepared using the software of HEC-RAS version 5.0.7 and the it’s output was used as material for preparing potential flood inundation maps. The potential flood inundation map was prepared by overlay method with the help of the Arc-GIS version 10.8 application. The research results show that the peak flood time is 7.43 hours with peak discharge for a 100 year return period of 1,542 m3/second. Flood inundation occurred in nine sub-Districts including Talang Empat District (552,819 ha), Karang Tinggi (391,648 ha), Selebar (24,118 ha), Singaranpati (95,806 ha), Ratu Samban (6,838 ha), Ratu Agung (212,173 ha), Sungaiserut (541,659 ha), Muara Bangkahulu (395,495 ha), and Pondok Kubang (197,167 ha). The conclusion of the research is that the model developed is able to answer peak times, area and water level of inundation as well as potential locations that will be flooded.